Manfaat Edukasi terhadap Penurunan Kadar Kolesterol Pasien Obesitas Rumah Sakit Mardi Waluyo - Mertha Dewi; Firhat Esfandiari; Ratna Purwaningrum; Muhamad Yunus (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Obesity is a disease caused by an imbalance between incoming and outgoing energy so that in the body there is an accumulation of fat tissue. One effort to reduce blood cholesterol can be done through consultation or counseling. The purpose of this study was to determine whether there is a relationship between the benefits of education with changes in lifestyle behavior to reduce cholesterol levels in obese patients at Mardi Waluyo Hospital in 2019. Method This study uses an observational analytic approach with a cross-sectional design. The sampling technique in this study used a purposive sampling method and obtained a total sample of 30 people. Data analysis using the T-Test Dependent test. The results are known to Obesity Patients aged 20-29 years as many as 3 people (10%), aged 30-39 years as many as 5 people (17%), aged 40-49 years as many as 9 people (30%), aged 50-59 as many as 8 people (26%) and aged 60-69 years as many as 5 people (17%) and most of the female sex as many as 22 people (73%). By conducting education on obese patients before and after it is very influential in reducing cholesterol levels